Epstein-Barr virus-encoded miR-BART11 promotes tumor-associated macrophage-induced epithelial-mesenchymal transition via targeting FOXP1 in gastric cancer - Song, Yali; Li, Qiao; Liao, Shan; Zhong, Kangying; Jin, Yaxiong; Zeng, Tingting (Virology (New York, N.Y.), 2020)
Gastric carcinoma (GC) is an Epstein-Barr virus (EBV)-associated malignancy characterized by early metastasis. Unlike that of cellular micro(mi)RNAs, the role of viral miRNAs in epithelial-mesenchymal transition (EMT) and metastasis in cancers has not been fully investigated. In this study, we elucidated the involvement of miR-BART11, an EBV-encoded viral miRNA, in the EMT and metastasis of GC cells. EBV-miR-BART11 upregulation can lead to downregulation of forkhead box protein P1 (FOXP1) in both tissues and cell lines of gastric carcinoma. Downregulation of FOXP1 might trigger the secretion of interleukin 1β (IL-1β), IL-6, and 1L-10 in cancer cells, resulting in poor survival of GC patients. We found that the observed EMT phenotypes resulted from the EBV-miR-BART11 overexpression-induced FOXP1 downregulation, which impacted the expression of the EMT-transcription factors E-cadherin and snail. We further demonstrated that conditioned medium-derived tumor-associated macrophages (TAMs) promoted phenotypic changes and expression of EMT-related molecules in GC cells. Additionally, EMT changes were significantly promoted in GC cells cultured in conditioned medium from TAMs infected with EBV-miR-BART11-containing lentivirus. On the contrary, GC cells cultured in conditioned medium from TAMs infected with FOXP1-carrying lentivirus showed little or no EMT change. Taken together, our results suggest that EBV-encoded viral miRNA BART11 downregulates the FOXP1 transcription factor, and promotes EMT by directly influencing gastric tumor cells or indirectly affecting the tumor microenvironment, which might, in turn, accelerate cancer invasion and metastasis, thereby affecting the survival and prognosis of patients.